2011
DOI: 10.1002/hep.24635
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin concentration and transferrin saturation before liver transplantation predict decreased long-term recipient survival

Abstract: Serum ferritin (SF) concentration is a widely available parameter used to assess iron homeostasis. It has been described as a marker to identify high‐risk patients awaiting liver transplantation (LT) but is also elevated in systemic immune‐mediated diseases, metabolic syndrome, and in hemodialysis where it is associated with an inferior prognosis. This study analyzed whether SF is not only a predictor of liver‐related mortality prior to LT but also an independent marker of survival following LT. In a dual‐cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 44 publications
(60 reference statements)
5
42
1
1
Order By: Relevance
“…Many studies have suggested the correlation of lower levels of iron modulation proteins and CLD, but this has not been adequately studied in liver failure patients. 31 In the present study, %SAT predicted early mortality and also correlated with incidence of organ failure in ACLF patients, which suggests its potential as a prognostic marker in these patients. Various studies in the past have shown an inverse correlation of serum hepcidin with tissue iron in patients with CLD, 32,33 but none pertaining to ACLF.…”
Section: Discussionsupporting
confidence: 70%
“…Many studies have suggested the correlation of lower levels of iron modulation proteins and CLD, but this has not been adequately studied in liver failure patients. 31 In the present study, %SAT predicted early mortality and also correlated with incidence of organ failure in ACLF patients, which suggests its potential as a prognostic marker in these patients. Various studies in the past have shown an inverse correlation of serum hepcidin with tissue iron in patients with CLD, 32,33 but none pertaining to ACLF.…”
Section: Discussionsupporting
confidence: 70%
“…The usefulness of SF as a predictor of a poor outcome has previously been reported in patients before and after LT. 29,30 For example, Weism € uller et al 30 reported that the SF concentration not only predicts pre-LT mortality, but also death following LT. In addition, they reported that patients with high pre-LT SF values required a significantly longer time in the ICU, indicating a higher degree of morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that iron overload was responsible for the relationship between the SF level and outcome. 30 High SF levels accompany a great many diseases, and the corollary of this is that iron-induced hydroxyl radical formation leading to oxidative damage is likely to be a contributory factor in all of them. Similar to the past report, the high-SF group in the present study showed a poorer prognosis than the low-SF group in the present study (94.0% versus 97.9%; P 5 0.322).…”
Section: Discussionmentioning
confidence: 99%
“…These lines of evidence suggest that iron is an important culprit in thepathogenesis of liver cirrhosis. [5,6] In some previous studies, it has been shown that increased ferritin has significant prognostic value in chronic liver disease. Serum ferritin level has recently been reported to associate with early mortality in patientswith liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%